USE OF DRONES IN THE CONTROL OF HAZARDOUS PESTS OF WHEAT (Modern American Journal of Biological and Environmental Sciences, 2025)
This paper presents the results of experiments conducted in 2025 at the Tashkent Experimental Station of the Cereal and Legume Crops Research Institute to evaluate the effectiveness of using drones for the application of chemical and biological preparations against the dangerous wheat pest Olema melanopus (cereal leaf beetle). The studies assessed the efficacy of chemical insecticides containing lambda-cyhalothrin and imidacloprid, as well as the microbiological preparation “Bioturin,” based on the entomopathogenic bacterium Bacillus thuringiensis. The results showed that the chemical preparations provided 85.9–95.0% efficacy, while the biological preparation achieved 75.6–83.3% biological efficiency.